New records and descriptions of Ichneumonidae (Hymenoptera) from Mexico - Khalaim, Andrey I.; Kasparyan, Dmitri R.; López-Ortega, Maurilio (Zootaxa, 2018)
Based on a large quantity ichneumonid material collected mainly from the Mexican states of Veracruz and Quintana Roo, faunistic records of 79 species belonging to subfamilies Acaenitinae, Banchinae, Cryptinae, Cylloceriinae, Labeninae, Lycorininae, Microleptinae, Pimplinae, Tersilochinae, and Tryphoninae are provided. Three species are described as new to science: Latosculum ortegai Kasparyan & Khalaim, sp. nov. (Cryptinae), Eusterinx madorae Khalaim & Kasparyan, sp. nov. (Microleptinae) and Neotheronia veracruzana Khalaim, sp. nov. (Pimplinae). Two genera, Nipponaetes Uchida (Cryptinae) and Meggoleus Townes (Tersilochinae), and six species, Nipponaetes hansoni (Gauld) (Cryptinae), Lycorina moralesi Gauld (Lycorininae), Neotheronia murilloi Gauld (Pimplinae), Meggoleus pampahermosensis Alvarado (Tersilochinae), Phytodietus moragai Gauld, and Zagryphys zulaya Gauld (Tryphoninae), are first records from Mexico. Females of three species, Cestrus tenuiventris (Cresson), Mallochia macula Kasparyan & Ruíz-Cancino (Cryptinae), and Phytodietus moragai Gauld (Tryphoninae), are recorded and described for the first time.